Predicting Physical Activity Behaviours Among Chinese University Students: An Application Of Expanded Health Action Process Approach - Peng, Sanying (2024)
Insufficient physical activity (PA) among Chinese university students has become widespread and is a major cause of their low levels of physical fitness and various health problems. Effectively promoting PA requires accurately identifying psychological determinants and understanding the psychological mechanisms underlying PA formation. This study investigates the intrapersonal and interpersonal psychological predictors of PA behaviours among Chinese university students using the expanded Health Action Process Approach (EHAPA). A stratified random cluster sampling technique was employed to collect survey responses from 1,143 participants across six universities in five cities in southern Jiangsu, China. An explanatory sequential mixed methods design was used, beginning with a quantitative survey followed by qualitative interviews to explain the quantitative findings. For the quantitative research, ANOVA was conducted using IBM SPSS 26 to examine mean score differences in EHAPA constructs across different PA level groups and mindset groups. Structural equation modelling using IBM AMOS 26 evaluated predictors of PA behaviour and the mediating effects of planning. Multiple-group analysis examined the moderating effects of gender, Body Mass Index (BMI), and mindset group on the direct pathways predicting PA behaviour. The results show significant differences in maintenance self-efficacy (MSE), planning, social support (SS), and recovery self-efficacy (RSE) among different PA level groups.